Clinical and epidemiological profile of patients admitted to a COVID-19 Maternal ICU in the city of Teresina-PI - Loiola, Kátya Coeli da Costa; Evangelista, Bruna Oliveira; Alves, Natália de Sousa (Seven Editora, 2023)
Objective: To trace the clinical and epidemiological profile of pregnant and postpartum women admitted to the COVID-19 intensive care unit in a highly complex maternity hospital in the city of Teresina-PI. Methods: This is a quantitative, descriptive, retrospective chart review study carried out in a maternity hospital located in the city of Teresina-PI. The medical records of pregnant women with a clinical or serological diagnosis of COVID-19 were included. Records with a lot of incomplete data (more than 20), patients without a diagnosis of COVID-19 and whose symptoms appeared after childbirth were excluded. Results: The total sample of this study consisted of 43 medical records of patients who met the established criteria, the majority being women aged between 18 and 30 years (60.4%; N=26), weighing more than 65 kg (60.4%; N=26), multigravida (55.8%; N=24), who had prenatal consultations (88.3%; N=38) and had at least one complication during pregnancy (67.4%; N=29). The most frequently reported clinical manifestations were dyspnea (95.3%; N=42) and cough (81.3%; N=35). In addition, the survey revealed a high rate of premature birth (80%; N=20) and caesarean section (100%; N=25). 69.7% (N=30) of the sample required ventilatory support. Further studies are needed to understand the true profile of this population and the other consequences that the disease has for pregnant women. DOI:https://doi.org/10.56238/sevened2023.004-029